RIPK2 induces docetaxel resistance in prostate cancer through the NF-κB/P-gp signaling pathway - Shaoqiang Xing; Zhaoliang Xu; Sheng Zeng; Minghao Yue; Wenzhou Xing; Qian Liu (PLoS ONE, 2026)
Chemoresistance is a reason for treatment failure in prostate cancer. Receptor-interacting protein kinase 2 (RIPK2) has been shown to play a role in drug resistance in various cancers; however, its role and the underlying mechanism of chemoresistance in prostate cancer are unclear. We analyzed data from The Cancer Genome Atlas for RIPK2 expression in prostate cancer and its association with clinicopathological features. We also elucidated the role and mechanism of action of RIPK2 in prostate cancer cell resistance to docetaxel (DTX). The results showed that RIPK2 expression was upregulated in prostate cancer tissues and was associated with poor pathological grading. RIPK2 was also upregulated in 22RV1/DTX, C4-2/DTX, PC-3/DTX, and DU145/DTX cell lines and involved in DTX resistance. Mechanistic experiments revealed that RIPK2 was involved in DTX resistance by upregulating P-glycoprotein (P-gp) expression through the activation of the NF-κB signaling pathway. Xenograft tumor experiments confirmed that inhibition of RIPK2 or P-gp enhanced the efficacy of DTX in suppressing PC-3/DTX growth. Taken together, these results suggest that RIPK2 mediates DTX resistance in prostate cancer cells through the NF-κB/P-gp signaling pathway. RIPK2 and its downstream signaling molecules are potential targets for the treatment of chemoresistant prostate cancer.